2021
DOI: 10.1097/mat.0000000000001402
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Leakage From the Gas Outlet Port During Extracorporeal Membrane Oxygenation for COVID-19

Abstract: Patients with the coronavirus disease 2019 (COVID-19) sometimes develop refractory respiratory failure and may require venovenous extracorporeal membrane oxygenation (VV-ECMO). It is known that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is sometimes present in the blood of COVID-19 patients. VV-ECMO is often used for several weeks, and plasma leaks can occur, albeit rarely. Hence, in terms of infection control, a concern is that SARS-CoV-2 may leak from the gas outlet port of the oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Although the output of our study may not provide direct evidence, it provides novel insights to ECMO support of COVID-19 critically ill patients. From our research and other studies [ 2 , 29 ], SARS-CoV-2 is highly likely to permeate the membrane transporting from the patient’s blood to the gas side, and may diffuse from the gas side outlet port of ECMO.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although the output of our study may not provide direct evidence, it provides novel insights to ECMO support of COVID-19 critically ill patients. From our research and other studies [ 2 , 29 ], SARS-CoV-2 is highly likely to permeate the membrane transporting from the patient’s blood to the gas side, and may diffuse from the gas side outlet port of ECMO.…”
Section: Discussionmentioning
confidence: 54%
“…During the current COVID-19 pandemic, it has been reported that the plasma components from the gas outlet port of the membrane oxygenator became yellow foam and positive PCR test results were obtained from the gas outlet port of the membrane oxygenator [ 2 , 29 ]. This is due to the fact that SARS-CoV-2 in plasma may permeate the hollow fiber membrane and aerosol diffusion occurs from the gas outlet port [ 29 ]. Therefore, in ECMO support for COVID-19 patients, it must be recognized that there is the risk of ECMO infection due to extra-circulatory spread of the SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen diffusivity in water is 2.76 × 10 −9 m 2 /s, and glucose diffusivity in water is 9.30 × 10 −10 m 2 /s (the values in the literature). The values calculated based on the model [19,21] Permeability (P m ) of SARS-CoV-2 (4) [m/s] NA 3.1 × 10 −9 3.3 × 10 −10…”
Section: Determination Of Pore Diameter Surface Porosity and Sars-cov...mentioning
confidence: 99%
“…(3) Oxygen diffusivity in water: 2.76 × 10 −9 m 2 /s, glucose diffusivity in water 9.30 × 10 −10 m 2 /s (the value in the literature) [21]. (4) Calculated oxygen diffusivity in water using this model 3.26 × 10 −9 m 2 /s (molecular diameter 0.2 nm), glucose diffusivity in water 4.68 × 10 −10 m 2 /s (molecular diameter 0.7 nm). NA; not available.…”
Section: Determination Of Pore Diameter Surface Porosity and Sars-cov...mentioning
confidence: 99%